Effect of Malva sylvestris cream on burn injury and wounds in rats - Ebrahim Nasiri; Seyed Jalal Hosseinimehr; Mohammad Azadbakht; Jafar Akbari; Reza Enayati-fard; Soheil Azizi (Mashhad University of Medical Sciences, 2015)
Objectives: Burn injury is one of the most health-threatening problems in the world. Malva sylvestris (M. sylvestris) flowershave a high mucilage content and are used as a remedy for cut wound and dermal infected wounds in Iranian folklore Medicine. The purpose of this study was to investigate the effect of M. sylvestris cream on the second degree burn injury in rats. Materials and Methods: Five groups of 10 rats per group were burned with hot metal plate. Animals were administrated divided as control, normal saline, standard silver sulfadiazine 1% (SSD), 5% M. sylvestris, and 10% M. sylvestris into separate groups. Wound area, percentage of wound contraction, and histological and bacteriological assessments were evaluated. Results: Wound sizes were not significantly different among groups on 1st and 3rd days after burn injury, while they were significantly different among groups after 7th day post-burn injury. The average areas of wounds on the 15th day were 7.5±2.9, 6.7±2, 10.5±1.6, 4.7±2, and 4.5±2 cm2 for base cream, normal saline, SSD, 5% M. sylvestris, and 10% M. sylvestris, respectively. The results of histology exhibited well-formed horizontally-oriented collagen fibers in MS topical treatment groups. Microorganisms existed in the SSD group were most probably Staphilococcus epidermitis and for NS group were staphylococcus saprophiteccus. Conclusion: M. sylvestris cream improved histological changes of tissue components in the process of healing when compared with SSD cream. Therefore, it can be used as a topical treatment agent for burn wound.